Spatial and Quantitative Analysis of Historical Pollution Incidents: Sulfur Dioxide Emissions from Copper Smelting during Japan's Modernization Era - Takahashi, Takuya; Inoue, Kazuya (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
During Japan’s modernization and westernization over a century ago, copper mining and smelting became a key export industry. However, the resulting sulfur dioxide emissions caused significant damage to crops and forests. Due to the limited availability of historical environmental records, this study utilizes the atmospheric dispersion simulation tool AIST-ADMER, developed by the National Institute of Advanced Industrial Science and Technology, to reconstruct pollution patterns associated with the Besshi Copper Mine in Ehime Prefecture. We assess the plausibility of the simulated dispersion patterns by examining their correlation with historical records of environmental damage and compensation. The results reveal a moderate correlation between simulated sulfur dioxide concentrations and compensation levels, whereas the correlation with recorded damage is relatively weak. Regression analysis further indicates that compensation amounts are significantly associated with both concentration levels and the proportion of forest land use. Applying this model to counterfactual scenarios, we estimate that relocating the smelting facilities to alternative sites, such as a coastal onshore site or a mountainous inland area which could have increased compensation payments by approximately three and five times, respectively. These findings shed light on how corporate decisions shaped responses to environmental damage and compensation, highlighting the complex trade-offs companies faced in managing pollution under evolving social and environmental pressures. This research fills a significant gap in the literature by establishing a quantitative framework that links simulated pollution patterns with historical evidence, enabling a deeper understanding of past environmental impacts and corporate responses.